Kajian Hukum Pemeriksaan Selaput Dara dari Perspektif Ham dan Ditinjau dari Sistem Hukum Negara - Purwanto Panji Sasongko; Wiend Sakti Myharto, Sofiana; Sofiana; Muhammad Rafi Razan Darmawan (Syntax Corporation Indonesia, 2023)
Hymen examination is synonymous with the 'virginity test' which is a controversial examination by medical professionals. One of the famous myths about virginity is that 'virginity' is proven by writing the appearance of